Inovasi Canting Elektrik Portabel untuk Meningkatkan Produktivitas Pengrajin Batik di Pekalongan dengan Memperhatikan Quality Function Development (QFD) - Yasin Aushaf Abdurrahman; Nabila Yudisha; Fauzan Hakim; Rayhan Bramantyo; Nashwa Bayu Tsabitha; Adam Cahya Soeprapto (Populer: Jurnal Penelitian Mahasiswa, 2024)
The portable electric canting innovation has been developed to enhance the productivity of batik artisans in Pekalongan by considering Quality Function Deployment (QFD). This research aims to address the challenges faced in the traditional batik-making process, which is often time-consuming and labor-intensive. The research method employed includes identifying user needs, developing questionnaires, and analyzing data to evaluate user satisfaction with the electric canting. The results indicate that the portable electric canting can improve efficiency and comfort in the batik-making process while meeting users' needs for a practical and high-quality tool. Thus, this innovation is expected to contribute to the preservation of batik art in Indonesia.